2017
DOI: 10.1080/13603116.2017.1414888
|View full text |Cite
|
Sign up to set email alerts
|

Re-theorising inclusion and reframing inclusive practice in physical education

Abstract: Inclusion remains a key political agenda for education internationally and is a matter that teachers across subject communities and phases of education are challenged to respond to. In physical education specifically, research continues to highlight that current practice often reaffirms rather than challenges established inequities. This paper critically explores the understandings of inclusion that contribute to this situation and addresses the challenge of advancing inclusion in physical education from conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 43 publications
4
53
0
5
Order By: Relevance
“…There is a need for a more fundamental change in PE and, accordingly, in PETE (Fitzgerald, 2005;Penney et al, 2018). It has been suggested that PETE should be informed by a social model perspective (Brittain, 2004;Lee, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a need for a more fundamental change in PE and, accordingly, in PETE (Fitzgerald, 2005;Penney et al, 2018). It has been suggested that PETE should be informed by a social model perspective (Brittain, 2004;Lee, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…One way of thinking differently about the problem (Bacchi, 2009) is to take cripistemologies (Johnson & McRuer, 2014) as a point of departure in shaping a new kind of PE, using the differences of bodies and minds as a source of knowledge (Lee, 2011). This would include a dismantling of ableism and 'an appreciation that there are many different ways of moving, being healthy and physically active and a commitment to this diversity being reflected in curriculum' (Penney et al, 2018(Penney et al, , p. 1071. As Slee (2018) highlights: 'difference is the normal condition of humankind' (p. 51); most people do not belong to the strict categories of disabled or able-bodied but are situated somewhere in between (Campbell, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many courses observed a prevailing assumption was that 'if one is involved, one will learn' (Thomas 2013, 483) (i.e. will develop motor skills) without much elaboration on the content and purpose of the PE curriculum, which researchers often portray as gendered, culturally specific and narrowly conceived (Penney et al 2018). In the context of seeking to support individual learning progress, the most powerful approach was differentiated instruction.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple interpretations of inclusion, alongside a lack of knowledge and research on what inclusive PE looks like in practice (Fitzgerald 2012) are important issues that this research sought to respond to. Following Penney et al (2018), we point to the merit of DeLuca's (2013) framework, comprising four approaches to inclusionnormative, integrative, dialogical and transgressiveas a means of articulating the complexity and diversity of approaches that are variously positioned as 'inclusive'.…”
Section: Meanings Of and Approaches To Inclusionmentioning
confidence: 99%